2020
DOI: 10.1007/s10858-020-00346-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic 15N{1H} NOE measurements: a tool for studying protein dynamics

Abstract: Intramolecular motions in proteins are one of the important factors that determine their biological activity and interactions with molecules of biological importance. Magnetic relaxation of 15N amide nuclei allows one to monitor motions of protein backbone over a wide range of time scales. 15N{1H} nuclear Overhauser effect is essential for the identification of fast backbone motions in proteins. Therefore, exact measurements of NOE values and their accuracies are critical for determining the picosecond time sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Residues with the complete set of 15 N-R 1 , 15 N-R 2 , and { 1 H}- 15 N NOE parameters from two fields were subjected to model-free analysis (MFA). The dynamics interpretation based on the collected 15 N spin relaxation data was performed according to our previous approaches 54,64,65 . In short: a fully anisotropic model of motion was applied for all proteins, with the assumption of C2 symmetry for each homo-dimer resulting in four global parameters, D 1 , D 2 , D 3 and γ Euler angle (while α = β = 0 o ).…”
Section: Relaxation Measurements and Btb Domain Dynamics Analysismentioning
confidence: 99%
“…Residues with the complete set of 15 N-R 1 , 15 N-R 2 , and { 1 H}- 15 N NOE parameters from two fields were subjected to model-free analysis (MFA). The dynamics interpretation based on the collected 15 N spin relaxation data was performed according to our previous approaches 54,64,65 . In short: a fully anisotropic model of motion was applied for all proteins, with the assumption of C2 symmetry for each homo-dimer resulting in four global parameters, D 1 , D 2 , D 3 and γ Euler angle (while α = β = 0 o ).…”
Section: Relaxation Measurements and Btb Domain Dynamics Analysismentioning
confidence: 99%
“…Overall, the average hetNOE values for the domain bound to the peptides were around 0.8, indicating moderate local protein motions on the picosecond timescale ( Kharchenko et al, 2020 ), except in the η1-loop, which remained quite flexible with hetNOE values as low as 0.5–0.7 ( Figure 3 ). Generally, the binding of the H3K4me1 peptide results in movement restriction of the unstructured C-terminal I921-Q923 region.…”
Section: Resultsmentioning
confidence: 99%
“…Early characterization of ASHH2 CW domain binding behavior was performed by Hoppmann et al (2011) and later expanded with the structures of the bound state by Liu and Huang (2018) and Dobrovolska et al (2020) . The latter study and ligand titration experiments indicated that the CW domain sampled a range of conformations across the ns–ms timescale at equilibrium ( Kharchenko et al, 2020 ). Relaxation–dispersion experiments were then used to verify that some residues exhibited exchange on the timescales (i.e., up to ms) associated with conformational selection, a binding mode where ligands bind the correct conformation from a continuum of existing conformations ( Farber and Mittermaier, 2015 ; Dobrovolska et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We recorded a steady‐state backbone { 1 H}‐ 15 N heteronuclear NOE (het‐NOE) experiment on BAF250b ARID. The backbone { 1 H}‐ 15 N heteronuclear NOE experiment provides information on the motion of individual N‐H bond vectors 42 . Those that undergo motion faster than the overall tumbling of the molecules (in ps to ns timescale) show a decreased het‐NOE intensity relative to the average observed for most of the residues.…”
Section: Resultsmentioning
confidence: 99%
“…The backbone { 1 H}- 15 N heteronuclear NOE experiment provides information on the motion of individual N-H bond vectors. 42 Those that undergo motion faster than the overall tumbling of the molecules (in ps to ns timescale) show a decreased het-NOE intensity relative to the average observed for most of the residues. For instance, decreased het-NOE values are observed for the residues at the N-and C-terminal ends and flexible loop regions of the protein compared to the ordered and rigid regions that show positive heteronuclear NOE values of ~0.8.…”
Section: Nmr Chemical Shifts and Heteronuclear Noe Data Correlate Wit...mentioning
confidence: 95%